HYPERTHERMIA AND RADIATION IN TREATMENT OF HUMAN SQUAMOUS CELL CARCINOMA OF CERVIX XENOGRAFTED IN ATHYMIC MICE - RANA, M.W. (Journal of Ayub Medical College Abbottabad, 1988)
Cytological screening by the use of the Papanicolaou smear has significantly reduced the number of patients with advanced cervical cancers. Early detection, epidemiology, correct diagnosis and treatment of early stages of cervical lesions have also been effective in control and prevention of cervical cancers. But invasive carcinoma of the cervix is still an important aspect of the cervical cancer problem. The greatest enigma at this time is the etiology, or predisposing factors, i.e., role of male and role of herpes and papilloma viruses in the development of these lesions, which classifies it as a sexually transmissible disease.1"4 This and other psychological and socio-economic factors might hinder some patients from seeking early detection and prevention. There are still hundreds of cases with advanced lesions reported in literature. Beyond stage II, radiation and chemotherapy are the only treatment and may not be well tolerated by the patient. Serious complications due to radiation therapy occur most frequently in advanced stages of this disease because of high doses of radiation which are required to accomplish tumor control.5 It is, therefore, important to seek a broader selection of modes of treatment for this cancer, especially in advanced stages. It is now well established that hyperthermia kills cells in a manner as predictable and repeatable as radiation and chemotherapy agents.6 Unlike ionizing radiation, hyperthermia kills both hypoxic and well oxygenated cells.7 Furthermore, neoplastic cells tend to be more sensitive to hyperthermia than do normal cells.8 In addition, heat interacts with radiation and chemotherapeutic agents.9"10 The role of prostaglandin, prostaglandin analogues, and prostaglandin inhibitors in the treatment of cancer is still controversial. Misonidazol (RO-07--582) has been shown to be an electron affinic hypoxic cell sensitizer.11,13 It minimizes the effect of oxygen as a reason for failure in the radiation of hypoxic tumors. We report here the effect of hyperthermia, radiation and chemotherapeutic agents, used alone or in combination, on human carcinoma of the cervix transplanted into athymic (nude) mice, which may offer a broader selection for the treatment of this lesion in human patients.